The influence of non-organic farmers’ perception on the willingness to adopting organic farming of horticultural crops - Prakaash Nagarajah (2015)
Organic farming is a holistic crop production system which takes into account all the important agricultural aspects to produce healthy and safe produce. It helps to enhance and maintain the agro-ecosystem health while maintaining health of farmers, conserving the surrounding environment, preserving the beneficial organisms, protecting the welfare of workers and community and in addition to that, providing secure and quality food. The organic farming sector is experiencing many difficulties to develop extensively in Malaysia. The main problems are not identified and thus, no solution is designed to overcome the problem and develop the sector. A major reason for this negligence is because the level of awareness towards the concept of organic farming and organic food is still low among Malaysians. Due to the low demand in Malaysia, this drives the supply of organic foods downwards, reducing interest of farmers in organic farming. Secondly, the perception of conventional farmers towards organic farming is always negative and this prevents the farmers from exploiting the benefits of organic farming. Farmers often think that there is no significant difference between organic produce and conventional produce as this perception could be due to lack of agricultural knowledge. The issue of food security and food safety has always been bombarding the headlines in the agriculture sector. In recent years, the focus of most agriculturalists are more towards producing high yields and maximizing profit while aiming to achieve the self-sufficiency level of foods and acquire food security. The aspect of food safety is often left out and this leads to nutritious agricultural crops that are not perfectly safe with chemical leftovers and pesticide residues. Farmers are facing many challenges especially in terms of establishment and maintenance to adopt organic farming techniques to cultivate crops including for those who want to start with organic farming and convert from conventional farming to organic farming. The environment is often left out as physical development is dominating the minds of people. The consequences will be worse when the country is full of buildings and no more trees and greeneries. The only way to take care of people and the environment at the same time is by maintaining ecosystem health. The objectives of the study are to analyze and cover the topics of perception, factors of perceptions and the adoption related to the organic farming of horticultural crops among the non-organic farmers. The objectives include to determine the perception level of non-organic farmers regarding their knowledge, skills together with attitude and mentality towards organic farming, to investigate the factors of perception such as challenges faced by conventional farmers and recommend solutions to overcome challenges in adopting organic farming, to clarify the socio-demographic relationship between the perception level of non-organic farmers, the factors of perception and their adoption of organic farming, to analyze the correlation of the perception and the perceptional factors towards the willingness of respondents to adopt organic farming. All the objectives of the research have clearly been achieved successfully. The statistics software used for the data analysis was Statistical Package for the Social Science (SPSS) 21.0 version and three methods of analysis were applied which include descriptive analysis, chi-square analysis and correlation analysis. These techniques were chosen in line with the given objectives and the results obtained on the influence of perception on adoption are provided as follows. The total number of respondents in this study is 150 non-organic farmers, whom mainly practice conventional horticultural farming. From the total of 150 selected respondents, 50 respondents are chosen from the top 3 states with the highest horticultural crop production in Malaysia, which is Pahang, Johor and Perak. It means, each state is represented by 50 farmers. These respondents were interviewed via a structured questionnaire to determine the socio demographic profile which includes, respondents’ background information and farm profile, the perception of the non-organic farmers which can be further subdivided to level of knowledge, level of skills and level of attitudes and mentality, followed by the factors of perception that include challenges and the suggestions and recommendations and finally the adoption of organic farming. This study was carried out to study on the perception of non-organic farmers’ towards organic farming and how the perception and its factors can influence the farmers’ decision in adopting organic farming of horticultural crops. This is an attempt to identify the current status of the organic agriculture in Malaysia and analyze how efforts can be taken via the perception of the conventional farmers that can lead to the adoption of organic farming. In this study, descriptive analysis was used to describe the variables in terms of frequencies distribution, mean and percentage. Chi-square test was used to determine the presence of a relationship between the socio demographic variables and the other parameters in the study such as perception, factors of perception and the adoption. Results of the chi-square revealed the presence of relationship between the socio demographic variables linking with the perception level and factors of perception, but not with the adoption. Then, the correlation analysis was used to determine the strength of the relationship between the, perception, factors of perception and adoption of organic farming and it showed a positive correlation with adoption. Future study on this topic can be carried out by widening the scope of this research by studying the perspective of organic farmers, consumers, organizations related to organic farming and the government while increasing the area of coverage and respondents to make the results more precise. A change in data collection technique is also suggested to improve the questionnaire design with more graphical representation and addition of qualitative research by interviewing respondents. Another recommendation is to focus more on the plan of action such as implementing the adoption because the influence of perception on adoption was the first step in this research.
Project paper (B.Agric.Sc.) - Universiti Putra Malaysia, 2015.